The Gastric Ganglion of Octopus vulgaris: Preliminary Characterization of Gene- and Putative Neurochemical-Complexity, and the Effect of Aggregata octopiana Digestive Tract Infection on Gene Expression - Baldascino, Elena; Di Cristina, Giulia; Tedesco, Perla; Hobbs, Carl; Shaw, Tanya J.; Ponte, Giovanna; Andrews, Paul L. R. (Frontiers in Physiology, 2017)
The gastric ganglion is the largest visceral ganglion in cephalopods. It is connected to the brain and is implicated in regulation of digestive tract functions. Here we have investigated the neurochemical complexity (through in silico gene expression analysis and immunohistochemistry) of the gastric ganglion in Octopus vulgaris and tested whether the expression of a selected number of genes was influenced by the magnitude of digestive tract parasitic infection by Aggregata octopiana. Novel evidence was obtained for putative peptide and non-peptide neurotransmitters in the gastric ganglion: cephalotocin, corticotrophin releasing factor, FMRFamide, gamma amino butyric acid, 5-hydroxytryptamine, molluscan insulin-related peptide 3, peptide PRQFV-amide, and tachykinin–related peptide. Receptors for cholecystokininA and cholecystokininB, and orexin2 were also identified in this context for the first time. We report evidence for acetylcholine, dopamine, noradrenaline, octopamine, small cardioactive peptide related peptide, and receptors for cephalotocin and octopressin, confirming previous publications. The effects of Aggregata observed here extend those previously described by showing effects on the gastric ganglion; in animals with a higher level of infection, genes implicated in inflammation (NFκB, fascin, serpinB10 and the toll-like 3 receptor) increased their relative expression, but TNF-α gene expression was lower as was expression of other genes implicated in oxidative stress (i.e., superoxide dismutase, peroxiredoxin 6 and glutathione peroxidase). Elevated Aggregata levels in the octopuses corresponded to an increase in the expression of the cholecystokininA receptor and the small cardioactive peptide-related peptide. In contrast, we observed decreased relative expression of cephalotocin, dopamine β-hydroxylase, peptide PRQFV-amide, and tachykinin-related peptide genes. A discussion is provided on i. potential roles of the various molecules in food intake regulation and digestive tract motility control, and ii. the difference in relative gene expression in the gastric ganglion in octopus with relatively high and low parasitic loads and the similarities to changes in the enteric innervation of mammals with digestive tract parasites. Our results provide additional data to the described neurochemical complexity of O. vulgaris gastric ganglion.